Aristophanea studies on the text of Aristophanes - Wilson, Nigel Guy 1935- (Oxford University Press, 2007)
Commentary on the plays of Aristophanes: Acharnenses (Acharnians); Equites (Knights); Vespae (Wasps); Lysistrata; Thesmophoriazusae (Women celebrating the Thesmophoria); Ecclesiazusae (Assemblywomen); Plutus (Wealth)
Published online: February 2018
Keywords: Aristophanes / Criticism, Textual; Aristophanes -- v445-v385; Greek drama (Tragedy) / Criticism, Textual; Textkritik; Komödie; Aufsatzsammlung